Financial Communication in the Context of Corporate Social Responsibility Growth - Alexandru Avram; Ana-Cristina Nicolescu; Costin Daniel Avram; Roxana Loredana Dan (Amfiteatru Economic)
In this paper, we studied the manner in which, at the same time with the growth of companies' corporate 23 At the same time, financial communication has benefited from the emergence of a new communication channel, namely the Internet, which has allowed an unprecedented opening of financial and accounting information towards an extremely diverse audience. Thus, social responsibility and sustainable development have become subjects extensively addressed in the specialized literature, focusing on three main directions: environmental protection, social responsibility of companies and sustainable economic development, all under the attention of a public that has grown exponentially with the help of easy access to information via the Internet. Given the increasing access of the population to the Internet, we intend to study to what extent the concerns of corporations to increase the corporate governance index, along with the high level of R & D expenditures produce concrete effects on Biodiesel production, recycling and waste measured in kg / capita as essential components of the bio-economy. Using a model of Autoregressive Panel Vector type (PVAR), we have identified the relations that develop between the increasing access to internet of the population and the increase of corporate governance index and level of R&D expenditures on recycling, waste and production of biodiesel in the European Union.